Efektivitas Pelaksanaan Ibadah Daring Ditinjau dari Roma 12:1-2 - Dicky Dominggus (Sekolah Tinggi Theologia Nazarene Indonesia, 2020)
In 2020, the implementation of worship has changed the way from physical gathering to online worship. This is certainly a challenge for churches that are accustomed to direct worship and must get used to it. From the Bible, the text of Romans 12: 1-2 is the biblical foundation for worship. This article aims to look at the effectiveness of online worship based on Romans 12: 1-2. The method used in this research is a qualitative method with a grammatical-historical approach. Based on the research conducted, worship actually talks about everyday life. Regarding online worship, online worship is a way to fellowship with God. Because online worship has the same essence as worship for physical gatherings, it is necessary to be serious in carrying out worship online.